2001
DOI: 10.1007/bf03353422
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different levels of dietary restriction on aging and survival in the Sprague-Dawley rat: Implications for chronic studies

Abstract: ABSTRACT. A study was undertaken to determine the effects of incremental levels of dietary restriction (DR) in rats. Survival, growth, reproductive, and dietary intake (DI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…19 Dietary restriction, even in slight degree, could produce beneficial effect. 20 The current study demonstrated that 20% and 40% of DR produce similar effects against stroke injury in MCAO rats (data shown in Supplementary Figure S1). …”
Section: Discussionsupporting
confidence: 61%
“…19 Dietary restriction, even in slight degree, could produce beneficial effect. 20 The current study demonstrated that 20% and 40% of DR produce similar effects against stroke injury in MCAO rats (data shown in Supplementary Figure S1). …”
Section: Discussionsupporting
confidence: 61%
“…In addition, the USA Food and Drug AdministraEffects of reduced food intake on toxicity study parameters in rats Tomoyuki Moriyama, Shigeharu Tsujioka, Takashi Ohira, Satoko Nonaka, Hisataka Ikeda, Hiroki Sugiura, Masayuki Tomohiro, Keiji Samura and Masaru Nishikibe tion (FDA) (Allaben et al, 1996;Duffy et al, 2001) and the Society of Toxicologic Pathology (Nold et al, 2001) have stated that dietary optimization is needed in rodent bioassays. We have been conducting toxicity studies in the dietary-optimized rat model, and frequently faced the dilemma of whether the observed changes were a direct effect of drug or secondary to decreased food intake.…”
Section: Introductionmentioning
confidence: 99%
“…Calorie restriction (CR), also known as dietary restriction, food restriction and energy restriction, is referred to as the regimen of inducing under-nutrition without malnutrition by reducing food intake 10%~40% below the ad libitum level (Duffy et al 2001). It is a simple and reproducible method widely used in research for delaying the aging process, extending average or maximum lifespan and preventing the onset of aging-related diseases such as diabetes, obesity, cancer, hypertension, cardiovascular diseases, heart failure and so on (Xiang and He 2011).…”
mentioning
confidence: 99%